Computer-assisted English language learning technology for undergraduate university students - Sehar Naveed Rajput; Syed Hyder Raza Shah (Northern Negros State College of Science and Technology (NONESCOST), 2021)
The study purposes at examining the computer-assisted English language learning technology for undergraduate university students. Computer-Assisted English Language Learning (CAELL) is an emerging trend that has highly impacted traditional theories of learning and teaching foreign languages. This new trend has introduced innovative techniques and the latest pedagogies for teachers and students of all levels. This is an attempt to look at teaching and learning practices through CAELL. The study is conducted in the mixed method in which sequential exploratory design is employed. A random sampling technique is used to select the population for this research. Data is collected from both teachers and students. 10 English language teachers are requested for semi-structured interviews to explore the CAELL teaching practices. Furthermore, a questionnaire is adapted for 146 undergraduate students of Shaheed Benazir Bhutto University (SBBU) Shaheed Benazirabad and its campuses. Qualitative data is thematically analyzed and Statistical Package for Social Sciences software (SPSS) 20th version is used to analyzed quantitative data. The findings indicate that there is a positive effect of CAELL technology among university students and teachers. Among four skills of language, students effectively improve their listening skills by using CAELL. This new trend increases students' motivation and eases them to learn English without pen and paper. Students prefer to use CAELL but most of the participants are unaware of using CAELL because of lack of facilities. Teachers are of the view that effective English language teaching demands CAELL knowledge. Last but not least limitations and delimitations are identified and areas for further studies are recommended.